STRENGTHENING LEGAL PROTECTIONS AGAINST SOCIAL ENGINEERING IN DIGITAL BANKING: CHALLENGES, GAPS, AND RECOMMENDATIONS - Utami, Putu Devi Yustisia; Purwanti, Ni Putu (Masalah-Masalah Hukum, 2025)
Social engineering is a form of manipulation used by malicious actors in digital banking services, exploiting social interaction mechanisms that can lead to financial losses for customers. Under Article 55 of the Financial Services Authority Regulation on Consumer Protection, financial institutions are obligated to safeguard customer funds. However, these protections often fail during social engineering incidents. This study utilizes both normative and empirical legal research methods to analyze common social engineering schemes, such as the distribution of APK files containing malware, phishing, pretexting, baiting, and quid pro quo. Consumer protection in the banking sector is regulated by several legal instruments, including the Consumer Protection Act, Financial Sector Development and Strengthening Act, and Financial Services Authority Regulation on Consumer Protection. Although these frameworks include fundamental consumer protection principles, they are inadequate in addressing the specific needs of customers affected by social engineering. Legal remedies for affected customers include filing complaints with banks or the Financial Services Authority, and pursuing litigation following fraud reports to the police, as stated in Article 378 of the Indonesian Criminal Code. The study recommends that the government issue more detailed implementing regulations under the Financial Services Authority's Consumer Protection framework to provide effective legal remedies for victims. Additionally, banks should implement financial literacy programs, and customers should exercise caution to avoid disclosing sensitive information in digital banking services.